Protein preparation, crystallization and preliminary X-ray analysis of Trypanosoma cruzi nucleoside diphosphate kinase 1 - Gómez Barroso, J. A. (International Union of Crystallography, 2010)
The flagellated protozoan parasite Trypanosoma cruzi is the aetiological agent of Chagas disease. Nucleoside diphosphate kinases (NDPKs) are enzymes that are involved in energy management and nucleoside balance in the cell. T. cruzi TcNDPK1, a canonical isoform, was overexpressed in Escherichia coli as an N-terminally poly-His-tagged fusion protein and crystallized. Crystals grew after 72 h in 0.2 M MgCl(2), 20% PEG 3350. Data were collected to 3.5 Å resolution using synchrotron X-ray radiation at the National Synchrotron Light Laboratory (Campinas, Brazil). The crystals belonged to the trigonal space group P3, with unit-cell parameters a = b = 127.84, c = 275.49 Å. Structure determination is under way and will provide relevant information that may lead to the first step in rational drug design for the treatment of Chagas disease.